THE ROLE OF PROVERBS IN READING LITERACY TEXTBOOKS - Qahhorova Sojida Bahodir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation:  This thesis analyzes the role and significance of proverbs in the process of developing students' speech. Proverbs embody the centuries-old wisdom and life experiences of the people, and incorporating them into the educational process expands students' vocabulary, enhances their expressive skills, and shapes their speech culture. The research examines effective methods of using proverbs, the pedagogical foundations of applying them in lessons, and their positive impact on students' speech activities. The results show that integrating proverbs into the educational process is an important factor in developing students' communicative competence.